طرق تدريس النحو ووسائلها التعليمية بجامعة فطاني- جنوب تايلاند: دراسة وصفية تحليلية - أونج آج، عنؤصان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study was conducted in order to identify methods of teaching Arabic language and grammar (Nahu), to find the most suitable methods of teaching Arabic grammar (Nahu) at Fatoni University, and to discover the role of educational methods and its importance in the teaching of Arabic grammar (Nahu), and to understand of the psychology of students of the university while learning this subject, as well as their suggestions about teaching methods in the University. The researcher followed descriptive analytical method and field inductive approach; he used the questionnaire as a tool for this research. The study's sample includes (50) male and female students of Department of Arabic Language at Fatoni University in Southern Thailand starting from the first year to fourth year, (10) male and female lecturers. The researcher adopted the statistical analysis on the value of percentage ratio and arithmetic average. He found that students and teachers are convinced to the reasonableness of teaching methods and educational means used in Fatoni University. It showed that students' satisfaction ranked (3.91) of the arithmetic average degree, while teachers recorded (3.64). The students suggested assimilation the local language in teaching the rules to make sure that students understand theoretically and practically by the students, and facilitating suitable notes of grammar (Nahu). On the other hand, teachers think that is important to create harmony between teachers and students and to ensure that the lessons got understood encourage students as classes theoretical and practical. The teachers called to engage the students and encourage them to participate in the classroom activities, and to use various educational means to achieve the desired learning goals.